Digital restoration workbook - Craig-McFeely, J; Lock, A (Digital Image Archive of Medieval Music, 2006)
Produced in conjunction with the AHRC ICT Methods Network for a AHRC ICT Methods Network workshop: "Digital Restoration for Damaged Documents" held on 29 June 2006.